Mastering and applying resolutions of the Party’s XIII Congress in teaching Marxism-Leninism philosophy in the universities - Trương Thị Xuân Hương (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Resolution of the 13th National Congress of the Communist Party of Vietnam had given direction: “The guiding ideology of the entire Party, people and army is steadfastly and creatively applying Marxism-Leninism and Ho Chi Minh’s thought, steadfast in the goal of national independence and socialism…”. Creating high-quality human resources, meetting the development requirements of the country in the current period the mastery and application of the Resolution of the 13th National Party Congress in teaching Marxism-Leninism in the universities is a requirement, a central task, meaningful in creating a change in awareness, unity of will and action among staff, lecturers and students, promote patriotism, self-reliance, and contribute to the successful implementation of the Congress’s Resolution.